Factors affecting the relative abundance of nuclear copies of mitochondrial DNA (Numts) in Hominoids (2012)
ABSTRACT: Although nuclear copies of mitochondrial DNA (numts) can originate from any portion of the mitochondrial genome, evidence from humans suggests that more variable parts of the mitochondrial genome, such as the mitochondrial control region (MCR), are under-represented in the nucleus. This apparent deficit might arise from the erosion of sequence identity in numts originating from rapidly evolving mitochondrial sequences. However, the extent to which mitochondrial sequence properties impacts the number of numts detected in genomic surveys has not been evaluated. In order to address this question, we: (1) conducted exhaustive BLAST searches of MCR numts in three hominoid genomes; (2) assessed numt prevalence across the four MCR sub-domains (HV1, CCD, HV2, and MCRF); (3) estimated their insertion rates in great apes (Hominoidea); and (4) examined the relationship between mitochondrial DNA variability and numt prevalence in sequences originating from MCR and coding regions of the mitochondrial genome. Results indicate a marked deficit of numts from HV2 and MCRF MCR sub-domains in all three species. These MCR sub-domains exhibited the highest proportion of variable sites and the lowest number of detected numts per mitochondrial site. Variation in MCR insertion rate between lineages was also observed with a pronounced burst in recent integrations within chimpanzees and orangutans. A deficit of numts from HV2/MCRF was observed regardless of age, whereas HV1 is under-represented only in older numts (>25 million years). Finally, more variable mitochondrial genes also exhibit a lower identity with nuclear copies and because of this, appear to be under-represented in human numt databases.